2019
DOI: 10.1186/s13018-019-1205-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of extra-articular scapula fracture fixation with distal humeral Y-type locking plate: a retrospective study

Abstract: Background This study aimed to compare the functional outcomes of the Y-type locking plate with the straight reconstruction locking plate for severe displaced scapular fractures. Methods This was a retrospective cohort study of 37 patients with severe displaced scapular body and neck fractures treated between July 2013 and October 2016 at the Hanzhong Central Hospital. Treatment selection was based on the surgeon’s experience and discussion with the patient. Sixteen pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…In addition, better internal fixation improves early functional recovery and reduces adhesive capsulitis caused by shoulder joint immobilization. 1,8,12,18,20,23 This study showed that the titanium anatomic plate outperformed the titanium reconstructive plate with respect to surgical duration, intraoperative blood loss, and shoulder joint function at 3 months postoperatively. There was no significant difference in shoulder ROM and patient satisfaction in all patients 1 year after the operation based on the Constant-Murley score and WOSI score.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, better internal fixation improves early functional recovery and reduces adhesive capsulitis caused by shoulder joint immobilization. 1,8,12,18,20,23 This study showed that the titanium anatomic plate outperformed the titanium reconstructive plate with respect to surgical duration, intraoperative blood loss, and shoulder joint function at 3 months postoperatively. There was no significant difference in shoulder ROM and patient satisfaction in all patients 1 year after the operation based on the Constant-Murley score and WOSI score.…”
Section: Discussionmentioning
confidence: 84%
“…There are a variety of plates to consider, including reconstructive plates, locking compression plates, distal radius T-plates, calcaneal plates, and miniplates. 1,8,12,17 Most of these plates do not conform to the anatomic shape of the scapula, creating intraoperative inconvenience as alignment with the surface of the scapula is difficult, resulting in only moderate fixation efficacy.…”
mentioning
confidence: 99%
“…The use of alternative fixation is well described in the literature with good to excellent results. 11,12,30 Non-anatomical plates, with or without K-wire/screw fixation and even plates designed to address a completely different fracture pattern at different anatomical sites, have been used to fix scapula fractures. Utilising different fixation techniques, as outlined in the literature, corroborates our observation that the current precontoured anatomical scapula plates might not be suitable to fit around all types of scapula fractures.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Limited implant options and pre-contoured plating systems have often led surgeons to use alternate fixation systems intended for other bones to fix scapular fractures. 11,12 Historically, several classification systems were proposed, attempting to guide the surgeon in decision-making and fracture management. The most used classification system was developed by the OTA Classification Committee in 1996 and revised ten years later.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of implants are available for fixation of these complex fractures. Some of the implants used for scapula fracture fixation reported in literature include locking compression plate, reconstruction plate, distal radius plate, distal humerus Y-type locking plate, T-plate, calcaneous deformed plate, and microplate [3,4,[7][8][9][10][11]. Aim of our study was to evaluate the functional outcome of extra-articular scapula fractures treated by open reduction and internal fixation using recon plates and T buttress plates.…”
Section: Introductionmentioning
confidence: 99%